Gamification in Accounting Learning: Can It Increase Student Motivation and Interest? - Meilani, Melan Nur; Julianti, Adelia Renggani; Drajat, Alvira Zulfa; Utami, Mega; Rozak, Rama Wijaya Abdul; Mulyani, Heni (Universitas Negeri Padang, 2023)
The research aims to determine the increase in students motivation and learning interest in using the gamification learning method. The research method used was a one group design experiment. The data source was obtained from research conducted on March 9, 2023 at one of the tenth grade vocational high school levels majoring in Accounting and Institutional Finance at a school in the city of Bandung by distributing questionnaires to students with closed answer forms. The results of the study show that learning using the gamification method can increase students’ motivation and interest in learning. This is evidenced by the decrease in the level of saturation in the learning process. The gamification method shows lower results, namely 27.71%. Meanwhile, in learning using conventional methods the saturation level reaches 33.71%. That is, the gamification method affects the enthusiasm of students who are able to reduce their boredom in learning activities. The valid value gets the full value, which is equal to the number of research subjects involved. This indicates that the gamification method affects students motivation and interest in reducing learning saturation.